Синтагматичні властивості параболізмів у сучасній німецькій мові - Заполовський, М.В. (Дрогобицький державний педагогічний університет імені Івана Франка, 2015)
The article is dedicated to the study of syntagmatics, represented in collocations of lexical and syntactic variations of biblical parables, as well as their textual modifi cations in German lexicographical sources. Intralinguistic context of these units was determined. Structural models of their compatibility according to grammatical classes were studied.
Keywords: Syntagmatic peculiaritie, lexical and syntactic variation, parabolism, compatibility, context